Association Between Hair Model and Shampooing Frequency with the Incidence of Acne Vulgaris - Puguh Riyanto; Olivia Jovina; Sari Satya Febriani (Riviera Publishing, 2025)
Acne vulgaris is a persistent, chronic inflammation of the pilosebaceous follicle. Hair itself is not directly related, but hair products and habits can trigger the onset of acne vulgaris. Objective: This research aims to determine the relationship between hairstyles and shampooing frequency and the incidence rate of acne vulgaris. This study was a descriptive observational study with a cross-sectional design. The research was conducted at a private clinic in Semarang from June 10 to 17, 2025. The sample consisted of 56 respondents selected using a purposive sampling method according to the research criteria. Data collected included age, acne incidence, acne severity, hairstyle, and shampooing frequency. Data analysis was conducted using SPSS. There was no significant association between hairstyle and shampooing frequency on the incidence of acne vulgaris, with p = 0.056 and p = 0.641, respectively. Thus, there was no meaningful relationship between hairstyle and shampooing frequency and the incidence of acne vulgaris